Citizenship Education in Preparing Nursing Students for the World of Work - Birgita Agnes Dwi Aprilia; Deswita Manuella; Kezia Victori Oktavia Hia; Novelia Cristiana (Immortalis Journal of Interdisciplinary Studies, 2025)
Civic Education has an important role in shaping the professional character of nursing students to face the challenges of a complex working world. Values ​​such as integrity, empathy, responsibility, and social awareness are important parts of nursing practice that require ethical and humanitarian sensitivity. However, the implementation of Civic Education in universities is often considered irrelevant to the needs of health professionals, so a more contextual and integrative learning approach is needed. This study uses a descriptive qualitative method with a literature study approach. (library research). Data were collected and analyzed from various relevant scientific literature on citizenship education, professional character formation, and nursing practice in the context of higher education. The analysis was conducted thematically to identify the form of effective implementation of Citizenship Education for nursing students. The results of the study indicate that Citizenship Education plays a significant role in forming professional character values ​​through the integration of citizenship values ​​in nursing learning practices. The implementation of case study-based learning, cross-disciplinary collaboration, and reflective approaches has proven effective in internalizing students' ethical and social values Civic Education learning that is designed adaptively and contextually is able to bridge the academic and nursing dimensions. The professionalism conclusion of this study emphasizes the need for reformulation of the Civic Education curriculum to be more relevant to the world of nursing. Civic Education not only forms a civic identity but also becomes an ethical foundation that strengthens the professionalism of health workers. This study is expected to be a foundation for the development of a Civic Education learning model that is more responsive to multidisciplinary dynamics in higher education.